2017
DOI: 10.1515/ijamh-2017-0079
|View full text |Cite
|
Sign up to set email alerts
|

Subjective social status and its relationship to health and health behavior: comparing two different scales in university students

Abstract: Background Little is known about the relationship between socioeconomic status (SES) and health in late adolescence. As it is difficult to measure SES in this age group directly, we used two subjective social status (SSS) scales with different reference groups for social comparison in the relatively homogeneous group of university students and analyzed the relationship with health and health behaviors. Methods We used two 10-rung ladders, a societal and a university one, to measure SSS in students (n = 689, 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
3
0
3
Order By: Relevance
“…Still, we believe that participants on the lower half (step 1–5) of the ladder (21% of the participants) were sufficiently represented to gain different perspectives on the subject. Compared with quantitative studies [ 10 , 11 ], our study had a similar or even higher representation of lower-status participants. The study was performed in Sweden, a high-income country ranking high on both the Human Development Index and the Gender Development Index [ 46 ], suggesting that the transferability primarily relates to similar cultures.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Still, we believe that participants on the lower half (step 1–5) of the ladder (21% of the participants) were sufficiently represented to gain different perspectives on the subject. Compared with quantitative studies [ 10 , 11 ], our study had a similar or even higher representation of lower-status participants. The study was performed in Sweden, a high-income country ranking high on both the Human Development Index and the Gender Development Index [ 46 ], suggesting that the transferability primarily relates to similar cultures.…”
Section: Discussionmentioning
confidence: 89%
“…In one ladder adolescents were asked to assess their position within their school; in the other they were asked to evaluate their families’ position in the society. Subjective social status in school has been associated with self-rated health, physical symptoms, anger, psychological distress, smoking, drinking and body mass index [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Joffer and colleagues [ 10 ] found that the proportion of adolescents with high self-rated health increased with higher rungs on a ladder measuring social status in school, and that boys perceived their own social status as higher than girls did.…”
Section: Introductionmentioning
confidence: 99%
“…Diese beschreibt eine soziale Leiter mit zehn Sprossen, auf der sich die Befragten verglichen mit der allgemeinen Bevölkerung hinsichtlich ihres wahrgenommenen Status platzieren. Zum anderen wurde eine universitätsspezifische Lei-ter aufgenommen, auf welcher sich die Befragten im Vergleich zu ihren Mitstudierenden einordnen [17]. Auch diese ergab sich in vorangegangenen Analysen als hilfreiches Messinstrument [17].…”
Section: Unabhängige Variablenunclassified
“…Zum anderen wurde eine universitätsspezifische Lei-ter aufgenommen, auf welcher sich die Befragten im Vergleich zu ihren Mitstudierenden einordnen [17]. Auch diese ergab sich in vorangegangenen Analysen als hilfreiches Messinstrument [17].…”
Section: Unabhängige Variablenunclassified
See 1 more Smart Citation